The efficacy of the old way/new way methodology on the correction of an automated technical error and its impact on the athlete’s psychological skills: case study in tennis - Lameiras, J.; Lopes de Almeida, P.; Garcia Mas, Alexandre (Cuadernos de Psicología del Deporte, 2015)
The aim of this study was to evaluated the efficacy of the Old Way/New Way methodology (Lyndon, 1989/2000) with regard to the permanent correction of a consolidated and automated technical error experienced by a tennis athlete (who is 18 years old and has been engaged in practice mode for about 6 years) in the execution of serves. Additionally, the study assessed the impact of intervention on the athlete’s psychological skills. An individualized intervention was designed using strategies that aimed to produce a) a detailed analysis of the error using video images; b) an increased kinaesthetic awareness; c) a reactivation of memory error; d) the discrimination and generalization of the correct motor action. The athlete’s psychological skills were measured with a Portuguese version of the Psychological Skills Inventory for Sports (Cruz & Viana, 1993). After the intervention, the technical error was corrected with great efficacy and an increase in the athlete’s psychological skills was verified. This study demonstrates the methodology’s efficacy, which is consistent with the effects of this type of intervention in different contexts.